Application of airborne LiDAR technology in geological hazard investigation in Huangpu District, Guangzhou City - Wenlong LI (Zhongguo dizhi zaihai yu fangzhi xuebao)
In recent years, airborne LiDAR technology has developed rapidly, allowing for the penetration of ground vegetation and the accurate acquisition of ground elevation, which is of great significance for precisely identifying geological hazard points. In order to understand the development characteristics of geological disasters in Huangpu District, Guangzhou, this study utilized airborne LiDAR technology to obtain three-dimensional point cloud and digital orthophoto images covering a total area of 526.5 km2 within district. Combined with traditional manual field investigation methods, the study identified the typical geological disaster development characteristics within the project scope. The interpretation results indicate that geological disasters within the investigation area are distributed in both surface and linear patterns, mainly concentrated in the hilly areas of the central and northern parts, with scattered or no distribution in other areas. There are 435 instances of geological disasters such as collapses and dangerous rock masses, 1027 instances of geological disasters such as landslides and unstable slopes, and 66 instances of low-frequency debris flow disasters that may be induced under extreme weather conditions, with landslides and unstable slope disasters being predominant. Additionally, the development pattern of geological disasters in the area exhibits a strong correlation with topography, geological conditions, engineering activities, and rainfall. Rainfall is notably significant in inducing geological hazards, with disasters occurring mainly within the range of monthly rainfall between 650 and 700 mm. The study demonstrates that airborne LiDAR technology can achieve the identification of geological disasters within the study area, providing valuable guidance and application value for guiding disaster identification, prevention, mitigation, and management.